O jogo na educação física da educação infantil : usos e apropriações em um CMEI de Vitória-ES - Klippel, Marcos Vinicius (2013)
This research study analyzes the uses and appropriations that children and their teacher make of the game, in the context of Physical Education classes, in a Municipal Center for Early Childhood Education at Vitória/ES. The theoretical-epistemological source adopted states that the game is a cultural manifestation productively consumed by practitioners of everyday school life, in a process of use which is the result of their tactics in face of the strategies imposed on them. It is guided by the sociological perspective that conceives children, who produce culture and knowledge, as citizens, subjects of rights, having their own social category, childhood. This research relies on Studies with the Quotidian as its theoreticalmethodological assumption and, as tools for the production of data, it relies on the semistructured interview, on the participatory observation, which was systematized in a journal, on pedagogical documents as well as on iconographic registers. The analyses indicate that there are no guidelines that organize the planning of teacher practice and show that her uses and appropriations of the game occur in an incidental and non-linear way, sometimes linked to the Developmental Approach, other times closer to a sociological conception, which recognizes children as producers of culture, respecting their generational needs. With respect to children’s uses and appropriations, the study highlights three contexts: a) when the game is the main activity of the class, a productive consumption by children is perceived, in which they transform play activities according to their interests and expectations, b) when the game is not the main activity of the class, tactical actions are identified, in which children create side games or entertaining contexts within the teacher's proposal, and c) in non directives classes, uses and appropriations that children make of the game denote their autonomy in the production of culture and knowledge. Regarding the participation of children in the coconstruction of classes, contradictions that reveal the various conceptions of childhood that go through the shared pedagogical practice and possibilities that value the child leading role in the teaching-learning process of Physical Education in Early Childhood Education are identified.